2016
DOI: 10.1071/ch16206
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Water-Catalyzed Formation of Levoglucosenone from Anhydrosugar Intermediates by Means of High-Level Theoretical Procedures

Abstract: Levoglucosenone (LGO) is an important anhydrosugar product of fast pyrolysis of cellulose and biomass. We use the high-level G4(MP2) thermochemical protocol to study the reaction mechanism for the formation of LGO from the 1,4:3,6-dianhydro-α-d-glucopyranose (DGP) pyrolysis intermediate. We find that the DGP-to-LGO conversion proceeds via a multistep reaction mechanism, which involves ring-opening, ring-closing, enol-to-keto tautomerization, hydration, and dehydration reactions. The rate-determining step for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…Previous studies have suggested that LG and DGP are key intermediates for LGO formation in H 3 PO 4 -catalyzed cellulose pyrolysis [11][12][13]18] . Based on these studies, the possible pathways responsible for LGO formation are provided in Fig.…”
Section: Formation Mechanism Of Lgo Under Non-catalytic Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have suggested that LG and DGP are key intermediates for LGO formation in H 3 PO 4 -catalyzed cellulose pyrolysis [11][12][13]18] . Based on these studies, the possible pathways responsible for LGO formation are provided in Fig.…”
Section: Formation Mechanism Of Lgo Under Non-catalytic Conditionsmentioning
confidence: 98%
“…LGO formation from DGP involves breakage of the 3,6-and 1,4acetal bonds, and formation of the 1,6-acetal bond. According to previously proposed pathways [12,13,15] , a possible pathway is illustrated in Fig. 4 (Path 9).…”
Section: Formation Mechanism Of Lgo Under Non-catalytic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is a well-known proton-transfer catalyst [45][46][47][48][49][50][51][52][53][54] and abundant in the biological system. It can be envisaged that participation of an explicit water molecule in all steps of both pathways may facilitate the proton transfers, thereby lowering energy barriers toward the transformations.…”
Section: Aza-michael Additionmentioning
confidence: 99%
“…[5] In catalysis research, Karton et al (University of Western Australia) report a detailed mechanistic study on the role of water in the formation of levoglucosenone from anhydrosugar intermediates, an important process in biomass conversion. [6] Wong et al (National University of Singapore) examine the catalytic mechanism of pentanidium-catalyzed asymmetric phase-transfer conjugate addition. [7] The origin of stereoselectivity is unravelled in their DFT study.…”
mentioning
confidence: 99%